2002
DOI: 10.1034/j.1399-3089.2002.02138.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐N‐glycolylneuraminic acid antibodies identified in healthy human serum

Abstract: The first and major clinical obstacle in xenotransplantation is antibody-mediated hyperacute rejection. Although human natural antibodies against Galalpha1,3Gal (Gal) antigens, which are common on porcine cells and organs, have been identified to play a major role in hyperacute rejection, other natural antibodies against non-Gal epitopes may be also involved in the process. Here, we present evidence suggesting that the majority of human anti-non-Gal antibodies are specific for carbohydrate structures carrying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
198
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(206 citation statements)
references
References 20 publications
4
198
1
Order By: Relevance
“…While this article was in preparation, another group independently reported a high prevalence of anti-Neu5Gc antibodies in normal human sera, using a different approach (39). The findings of both studies stand in contrast to previous reports of the prevalence of anti-Neu5Gc antibodies in normal humans, ranging only from 0-10% for the IgG class to 3.8-13.8% for the IgM class (40)(41)(42).…”
Section: Discussioncontrasting
confidence: 56%
“…While this article was in preparation, another group independently reported a high prevalence of anti-Neu5Gc antibodies in normal human sera, using a different approach (39). The findings of both studies stand in contrast to previous reports of the prevalence of anti-Neu5Gc antibodies in normal humans, ranging only from 0-10% for the IgG class to 3.8-13.8% for the IgM class (40)(41)(42).…”
Section: Discussioncontrasting
confidence: 56%
“…Recently, several reports have suggested that the possible epitopes on pig grafts recognized by human non-Gal antibodies include swine leukocyte antigen, N-glycolylneuraminic acid (NeuGc) epitopes (Hanganutziu-Deicher antigen, although this would not be a target in baboons because these animals also express this antigen), and Forssman antigen. 30,33,34 Further experiments are necessary to clarify the novel target epitope of non-Gal antibodies to consider other strategies to prevent non-Gal antibody-mediated rejection, including the deletion or modification of non-Gal epitopes by genetic engineering of the pig.…”
Section: Discussionmentioning
confidence: 99%
“…The total levels of IgG varied widely among individuals. Similarly, others found that 85% of healthy human subjects had anti-Neu5Gc Ig activity (29). The significance of such anti-Neu5Gc Abs in apparently healthy humans remains unknown, and their functional capabilities have not been demonstrated.…”
Section: Effects Of Natural Human Antibodies Against a Nonhuman Sialimentioning
confidence: 99%